Assessing shadow banking – non-bank financial intermediation in Europe - Laurent Grillet-Aubert; Jean-Baptiste Haquin; Clive Jackson; Neill Killeen; Christian Weistroffer (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
Owing to the disruptive events in the shadow banking system during the global financial crisis, policymakers and regulators have sought to strengthen the monitoring framework and to identify any remaining regulatory gaps. In accordance with its mandate, the European Systemic Risk Board (ESRB) has engaged in developing a monitoring framework to assess systemic risks in the European Union (EU) shadow banking sector. This assessment framework provides the basis for the EU Shadow Banking Monitor, which will be published each year by the ESRB. The framework also feeds into the ESRB's Risk Dashboard, internal risk assessment processes and the formulation and implementation of related macro-prudential policies. The ESRB's Joint Advisory Technical Committee (ATC)-Advisory Scientific Committee (ASC) Expert Group on Shadow Banking (JEGS) has accordingly engaged in: conducting a stocktake of relevant available data and related data gaps; defining criteria for risk mapping in line with the work of the Financial Stability Board (FSB) in this area; deriving indicators using this methodology for the purposes of the ESRB's risk monitoring and assessment. Shadow banking can be broadly defined as credit intermediation performed outside the traditional banking system. This is consistent with the definition used at the global level by the FSB. Against this background, this paper describes the structure of the shadow banking system in Europe and discusses a range of methodological issues which must be considered when designing a monitoring framework. The paper applies both an "entity-based" approach and an "activity-based" approach when mapping the broad shadow banking system in the EU. In turn, the analysis focuses primarily on examining liquidity and maturity transformation, leverage, interconnectedness with the regular banking system and credit intermediation when assessing the structural vulnerabilities within the shadow banking system in Europe. This approach appears the most appropriate for the purpose of assessing shadow banking related risks within the EU financial system. On this basis, the paper complements the EU Shadow Banking Monitor by providing further methodological detail on the development of risk metrics. The paper presents the analysis underpinning the construction of risk metrics for the shadow banking system in Europe and highlights a number of areas where more granular data are required in order to monitor risks related to certain market activities and interconnectedness within the broader financial system.
Keywords: G23; G18; 330; shadow banking; intermediation; systemic risk